An Unusual Presentation of T-Cell Lymphoblastic Lymphoma with Isolated Renal Involvement - Sultan Aydın Köker; Alper Koker; Adem Yasin Köksoy; Yasemin Kayadibi; Ülkü Gül Şiraz; Emine Tekin (Case Reports in Hematology)
The clinical presentation of Non-Hodgkin lymphoma (NHL) is frequently associated with the involvement of the abdomen and mediastinal lymphadenopathies, but rarely the kidney, ovaries, and testicles. Here, we report a rare case of T-cell lymphoblastic lymphoma (T-LBL) presenting with bilateral nephromegaly without acute renal failure (ARF) as the first manifestation. A 30-month-old boy was admitted to the department of pediatric nephrology exhibiting abdominal distension. Physical examination revealed bilateral renal palpation up to the inguinal region. Elevated lactate dehydrogenase (LDH) levels were detected in his blood. Bilateral diffuse enlarged kidneys with increased hypoechogenicity were found on abdominal ultrasonography. In the next step, contrast-enhanced computed tomography showed diffusely enlarged kidneys, which were compressing the intestinal bowels and midline structures. Renal biopsy demonstrated precursor T-LBL. We wish to report our patient with renal T-LBL presenting with diffuse renal enlargement, which has rarely been reported in the literature.